Study of Rainfall Trends and Frequency of Rainy Day over Parbhani: Impacts of Changing Rainfall Patterns on Rain-Fed Agriculture in Parbhani (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Changing climate unfavorably disturb the countries whose economy depends upon rain-fed agriculture since agricultural production is directly depends upon to the amount of rainfall. Taking this fact in consideration here the attempt was made to study trends of rainfall and rainy day of Parbhani city. Long term annual rainfall over Parbhani displayed significantly mounting trends for the period of 42 years. Rainfall trends of winter, summer and post Monsoon over Parbhani showed slightly growing trends while monsoon rainfall trends over Parbhani show slightly falling trends. January, March, April, July, October, November, December show increasing monthly rainfall trends. Maximum increase was seen for July and it was 2.80mm year while February, May, June, August, September show decreasing trends.